Melanocytic lesions of the central nervous system: a case series - VARELA-POBLETE, Jorge; VIDAL-TELLEZ, Aaron; CRUZ-QUIROGA, Juan Pablo; MONTOYA-SALVADORES, Francisca; MEDINA-ESCOBAR, Jaime (Arquivos de Neuro-Psiquiatria, 2022)
Background: Melanocytic lesions of the central nervous system (CNS) are an infrequent, broad and diverse group of entities, both benign and malignant, found in all age groups, with imaging findings ranging from well-circumscribed focal lesions to diffuse leptomeningeal involvement. On MRI, they are usually distinguished by a high signal on T1WI sequences, given the paramagnetic effect of melanin, thus making it difficult to differentiate among them. Objective: To describe the imaging and epidemiological characteristics of a retrospective series of CNS melanocytic lesions. Methods: MR images of 23 patients with CNS melanocytic lesions diagnosed between January 2012 and June 2018 were analyzed. Results: Most patients were female (14/23; 61%), with a median age of 47 years (range: 3 weeks to 72 years). The primary melanocytic lesions accounted for 8/19 cases (42.1%), which included neurocutaneous melanosis, meningeal melanocytomas and primary malignant melanomas. Secondary melanocytic lesions (metastatic) accounted for 10/19 cases (52.6%). There was one case of a tumor with secondary melanization, from a melanocytic neuroectodermal tumor of infancy. There were also four cases of primary ocular melanomas. The most frequent findings were the cerebral location, high T1WI signal and marked contrast-enhancement. Conclusions: The present review describes the wide variety of melanocytic lesions that could affect the CNS, emphasizing the MRI characteristics. Knowledge of the imaging, clinical and epidemiological characteristics of CNS melanocytic lesions is essential for their correct interpretation, given the significant overlap between lesion features and the variable prognosis.
Keywords: Central Nervous System Diseases; Melanosis; Neurocutaneous Syndromes; Magnetic Resonance Imaging; Neoplasm Metastasis